2013
DOI: 10.1038/leu.2013.262
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA theragnostics for the clinical management of multiple myeloma

Abstract: Theragnostics represent cutting-edge, multi-disciplinary strategies that combine diagnostics with therapeutics in order to generate personalized therapies that improve patient outcome. In oncology, the approach is aimed at more accurate diagnosis of cancer, optimization of patient selection to identify those most likely to benefit from a specific therapy and to generate effective therapeutics that enhance patient survival. MicroRNAs (miRNAs) are master regulators of the human genome that orchestrate myriad cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 75 publications
0
57
0
Order By: Relevance
“…A number of epigenetic modifications have been so far linked to cancer, including posttranslational modification of histones, DNA methylation, and the most recently discovered noncoding RNAs, which are currently considered key determinants in human cancer pathogenesis (2). In the last few years, a wealth of studies has shown deep dysregulation of miRNAs in human cancers, including multiple myeloma (3). Importantly, replacement of downregulated tumor suppressor (TS) miRNAs (4,5) or inhibition of oncogenic miRNAs (6)(7)(8) have demonstrated therapeutic value in multiple myeloma preclinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of epigenetic modifications have been so far linked to cancer, including posttranslational modification of histones, DNA methylation, and the most recently discovered noncoding RNAs, which are currently considered key determinants in human cancer pathogenesis (2). In the last few years, a wealth of studies has shown deep dysregulation of miRNAs in human cancers, including multiple myeloma (3). Importantly, replacement of downregulated tumor suppressor (TS) miRNAs (4,5) or inhibition of oncogenic miRNAs (6)(7)(8) have demonstrated therapeutic value in multiple myeloma preclinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…HDACs, key enzymes regulating the acetylation status of both histone-and non-histone proteins, are classified into 4 classes: class I (HDAC1, 2,3,8), class IIa (HDAC4, 5, 7, 9) and class IIb (HDAC6,10), class-III (SIRT1-7), and class-IV (HDAC11; ref. 12).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA studies (Table 1) MicroRNAs (miRNAs) constitute an important class of small RNAs, and understanding their functions has become a major area of research to develop potential targeted therapies [34].…”
Section: Dna-based Studiesmentioning
confidence: 99%
“…28 Literature advocates the deregulation of several miRNAs including miR-15, 16, 17, 20, 135, 30, 150, 160 and so on, which are regarded as hallmarks of tumor progression, clinical staging, prognosis, and drug responses in MM. [29][30][31][32][33][34] Basic mechanisms of miRNAs include positive or negative regulation of critical oncogenes or tumor suppressors, epigenetic modifications etc. that predominantly determines cell survival and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%